Translation : a guide to the practice of crafting target texts - Stella Cragie; Ann Pattison (London : Routledge, 2020)
"This practical guide by two experienced translators and translation tutors explores aspects of time, context and culture in a range of translated literary texts, including novels, memoirs, poems and plays. Reflective analytical sections are complemented by a variety of practical tasks that reflect the book's craft-based approach. Providing a dual focus on both analysis and creativity, this volume helps readers to develop two different skillsets required for translation: deconstruction and reconstruction. To learn how to analyse or deconstruct a source text, the tasks include translating and editing, comparison and analysis of source language texts and translations, and critiquing or improving target language texts produced by translators from different times. A range of creative writing challenges reveal the secrets writers use to hook their readers. Whatever language readers translate into, these insights will help them to find their own writer's voice, making them better equipped to recreate another author's voice, whatever the time or cultural context. This is the essential guide to improving target texts for all translators and students of translation"-- Provided by publisher
Keywords: Language arts (Higher) Correlation with content subjects; Translating and interpreting Methodology